Single-chain magnet behavior in a finite linear hexanuclear molecule. Issue 31 (15th July 2021) - Houard, Felix; Gendron, Frederic; Suffren, Yan; Guizouarn, Thierry; Dorcet, Vincent; Calvez, Guillaume; Daiguebonne, Carole; Guillou, Olivier; Le Guennic, Boris; Mannini, Matteo; Bernot, Kevin
Abstract : A stable hexanuclear molecule made of a Tb III building block and a substituted nitronyl-nitroxide radical show a single-chain magnet behavior despite being a finite molecule. Abstract : The careful monitoring of crystallization conditions of a mixture made of a Tb III building block and a substituted nitronyl-nitroxide that typically provides infinite coordination polymers ( chains ), affords a remarkably stable linear hexanuclear molecule made of six Tb III ions and five NIT radicals. The hexanuclear units are double-bridged by water molecules but ab initio calculations demonstrate that this bridge is inefficient in mediating any magnetic interaction other than a small dipolar antiferromagnetic coupling. Surprisingly the hexanuclears, despite being finite molecules, show a single-chain magnet (SCM) behavior. This results in a magnetic hysteresis at low temperature whose coercive field is almost doubled when compared to the chains . We thus demonstrate that finite linear molecules can display SCM magnetic relaxation, which is a strong asset for molecular data storage purposes because 1D magnetic relaxation is more robust than the relaxation mechanisms observed in single-molecule magnets (SMMs) where under-barrier magnetic relaxation can operate.